PERANAN KEPALA DESA DAN PARTISIPASI MASYARAKAT DALAM PEMBANGUNAN FISIK DI DESA AIKMEL KABUPATEN LOMBOK TIMUR PROVINSI NUSA TENGGARA BARAT - Ely Sukmana; Hishnul Islamy (J-3P (Jurnal Pembangunan Pemberdayaan Pemerintahan), 2019)
The Role of Village Heads and Community Participation in Physical Development in Aikmel Village, East Lombok Regency, West Nusa Tenggara Province. A Village Head is not likely to carry out his duties and responsibilities to make the village progress without the support and participation of the community. Leadership and community participation must be in line in order to create a harmonious conducive atmosphere so that the ideals of making the village better can be realized. The purpose of this study was to analyze the leadership of the village head and community participation, and to know the supporting and inhibiting factors in physical development in Aikmel Village. The method used in this study is a qualitative approach, complemented by observation, interview, documentation and triangulation techniques. The results of the study found that the Village Head as a motivator, driver, driver to achieve a development goal, and most people have participated in various fields of development. Keywords: leadership, community participation, Aikmel.